AN ANALYSIS OF LANGUAGE DOMAIN USED BY MAIN CHARACTERS IN THE CHILDE MOVIE - Sabrina Michelle Yaucob; Dona Rahayu Sugiharti (TANDA, 2026)
In a multilingual society, speakers tend to adjust their language use according to the social situations in which they interact. This study aims to analyze language domains and the factors underlying language differences in the movie The Childe. The data were collected from the dialogues of two main characters, Marco Han and the Childe. This research applies Fishman’s (1972) language domain theory and employs a descriptive qualitative method. The findings reveal 34 utterances containing language domain features. The family domain consists of 2 utterances, all produced by Marco Han; the friendship domain includes 16 utterances, with 9 produced by Marco Han and 7 by the Childe; the employment domain contains 14 utterances, with 2 produced by Marco Han and 12 by the Childe; and the social domain consists of 2 utterances, produced equally by both characters. The analysis shows that language use in the movie varies depending on place, interlocutor, and situation. Furthermore, several factors influence language differences and domain formation, including the characters’ background, setting, interlocutors, and the context and topic of interaction.